EFFECTS OF MUSIC AND MEMORY ON AGITATED AND AGGRESSIVE BEHAVIORS IN DEMENTIA: RESULTS FROM NURSING HOME PILOT STUDY. (16th November 2018) - McCreedy, E; Baier, R; Thomas, K; Mor, V
Abstract: Personalized music has been proposed as a non-pharmaceutical alternative for reducing agitated and aggressive behaviors among persons with dementia. One such intervention (MUSIC & MEMORY) has shown promise in demonstration projects and retrospective evaluation. In this pilot study, we tested the effects of MUSIC & MEMORY on agitated and aggressive behaviors for 43 people with moderate to severe cognitive impairment residing in four nursing homes. Agitation and aggression were measured by staff reporting of behaviors in the past week using the Cohen-Mansfield Agitation Inventory (CMAI), and direct observation of resident behaviors using the Agitated Behavior Mapping Instrument (ABMI). Among participants with pre- and post-intervention staff interviews (N=34), the average CMAI total score was 61.24 (standard deviation, SD: 16.32) before and 51.24(SD: 16.05) after music (paired t-test, p<.01). This finding was primarily driven by a decrease in verbally-agitated behaviors while using the music. Among those directly observed while using and not using the music (N=31), average total ABMI score without music was 4.4 (SD: 2.3) and with music, 1.6 (SD: 1.5) (paired t-test, p<.01). In addition to decreases in agitated behaviors, we observed significant increases in pleasure and interest while using the music. While these results are promising, they are limited by the pre-post study design, the potential for non-selective attrition, and the lack of blinding by staff and data collectors. These limitations will be addressed in the next phase of this research, a cluster randomized, controlled trial in 81 nursing homes throughout the US, scheduled to begin in Spring 2019.